Reframing organizations : artistry, choice, and leadership - Bolman, Lee G.; Deal, Terrence E. (Jossey-Bass, 2021)
"Reframing Organizations provides time-tested guidance for more effective organizational leadership. Rooted in decades of social science research across multiple disciplines, Bolman and Deal's four-frame model has continued to evolve since its conception over 25 years ago. This new seventh edition will be updated to include additional coverage of cross-sector collaboration, generational differences, virtual environments, globalization, sustainability, and communication across cultures. The instructor's guide will be expanded to provide additional tools for the classroom, including chapter summary tip sheets, mini-assessments, Bolman & Deal podcasts, and more. These recent revisions reflect the intersection of reader recommendations and the current leadership environment, resulting in a renewed practicality and even greater alignment with everyday application. The seventh edition combines the latest research from organizational theory, organizational behavior, psychology, sociology, political science and more. It will be updated to include advances in the field since the sixth edition, with new case studies for each frame, and will address the COVID-19 pandemic"--